Good Amil Governance, Digitalization, and Zakat Performance: Evidence from Indonesia - Nanang Setiawan; Azwar Cholili; Nur Kholis; Andriani Samsuri; Imam Muslih (Universitas Islam Negeri Ar-Raniry, 2026)
The sustainability of zakat institutions increasingly depends on their ability to strengthen governance, transparency, and service effectiveness in the digital era. In Indonesia, the rapid development of digital technology has created new opportunities for zakat institutions to improve accountability and institutional performance. This study examines the influence of good amil governance on zakat performance and explores the moderating role of zakat digitalization in Indonesian zakat institutions (Lembaga Amil Zakat/LAZ). A quantitative approach was employed through a survey of LAZ managers across Indonesia, and the data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings show that good amil governance contributes positively to zakat performance, particularly through stronger transparency, accountability, competence, and fairness in zakat management. Zakat digitalization also plays an important role in improving institutional performance by increasing efficiency, reporting accuracy, and stakeholder trust. Furthermore, digitalization strengthens the relationship between governance and zakat performance, indicating that technological capability enhances the effectiveness of governance practices within zakat institutions. The study contributes to the development of Sharia Enterprise Theory and the Technology–Organization–Environment (TOE) framework by emphasizing the strategic role of digital capability in strengthening governance and institutional performance. Practically, the findings encourage zakat institutions to pursue inclusive digital transformation while improving organizational readiness and digital literacy. ABSTRAK - Good Amil Governance, Digitalisasi, dan Kinerja Zakat: Bukti dari Indonesia. Keberlanjutan lembaga zakat semakin dipengaruhi oleh kemampuan institusi dalam memperkuat tata kelola, transparansi, serta efektivitas layanan, khususnya di tengah perkembangan era digital. Di Indonesia, kemajuan teknologi menghadirkan peluang strategis bagi lembaga zakat untuk meningkatkan akuntabilitas sekaligus kinerja kelembagaan. Penelitian ini bertujuan untuk menganalisis pengaruh good amil governance terhadap kinerja zakat serta mengkaji peran moderasi digitalisasi zakat pada Lembaga Amil Zakat (LAZ) di Indonesia. Penelitian ini menggunakan pendekatan kuantitatif melalui survei terhadap pengelola LAZ di berbagai wilayah Indonesia, dengan analisis data menggunakan metode Structural Equation Modeling–Partial Least Squares (SEM-PLS). Hasil penelitian menunjukkan bahwa good amil governance memberikan kontribusi positif terhadap kinerja zakat, terutama melalui penguatan aspek transparansi, akuntabilitas, kompetensi, dan keadilan dalam pengelolaan. Selain itu, digitalisasi zakat terbukti berperan penting dalam meningkatkan kinerja lembaga, khususnya melalui peningkatan efisiensi operasional, akurasi pelaporan, dan kepercayaan pemangku kepentingan. Digitalisasi juga memperkuat hubungan antara tata kelola dan kinerja zakat, yang menunjukkan bahwa kapabilitas teknologi mampu meningkatkan efektivitas implementasi praktik tata kelola. Secara teoretis, temuan ini memperkaya Sharia Enterprise Theory dan kerangka Technology–Organization–Environment (TOE) dengan menegaskan peran strategis kapabilitas digital dalam memperkuat tata kelola dan kinerja lembaga zakat. Secara praktis, penelitian ini mendorong perlunya transformasi digital yang inklusif, disertai peningkatan kesiapan organisasi dan literasi digital pada lembaga zakat.